1998
DOI: 10.1172/jci2004
|View full text |Cite
|
Sign up to set email alerts
|

Immortalization of osteoclast precursors by targeting Bcl -XL and Simian virus 40 large T antigen to the osteoclast lineage in transgenic mice.

Abstract: Cellular and molecular characterization of osteoclasts (OCL) has been extremely difficult since OCL are rare cells, and are difficult to isolate in large numbers. We used the tartrate-resistant acid phosphatase promoter to target the bcl -X L and/or Simian Virus 40 large T antigen (Tag) genes to cells in the OCL lineage in transgenic mice as a means of immortalizing OCL precursors. Immunocytochemical studies confirmed that we had targeted Bcl-X L and/or Tag to OCL, and transformed and mitotic OCL were readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…We have focused on Bcl-xL in the current study because its role in osteoclast survival has been repeatedly documented (12,14,17,37). In addition, we found that TNF stimulates expression of Bcl-xL, but not the other Bcl-2 family members we tested ( Figure 5).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We have focused on Bcl-xL in the current study because its role in osteoclast survival has been repeatedly documented (12,14,17,37). In addition, we found that TNF stimulates expression of Bcl-xL, but not the other Bcl-2 family members we tested ( Figure 5).…”
Section: Discussionmentioning
confidence: 78%
“…Macrophage colony-stimulating factor (M-CSF), a key survival factor for cells in the myeloid lineage, stimulates Bcl-xL expression (11,12). Osteoclasts generated from bone marrow cells of transgenic mice that overexpress Bcl-xL under the control of the tartrate-resistant acid phosphatase (TRAP) promoter are more resistant to serum withdrawal-induced cell death (13,14), demonstrating that Bcl-xL is involved in the control of osteoclast apoptosis.…”
mentioning
confidence: 99%
“…59 Taken together, we can conclude that tight control of translation seems to be necessary to provide BCL-2-like proteins and prolong Ocl survival. 60,61 Identification of responsible candidate proteins is the subject of further research. In summary, we describe for the first time a shared role for mTOR/S6K in the prosurvival signaling of osteoclastogenic cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…109 The generation of TRAP transgenic mice expressing the SV40 large T antigen, with or without the bcl-XL antiapoptotic gene, did not transform cells outside the osteoclast lineage. 14,54 The TRAP promoter has also been used to target overexpression of the c-fos gene to osteoclasts to generate a mouse model with some characteristics of Paget's disease. 11 Although Langerhans cells in the skin express TRAP, 49 the gene is also expressed in keratinocytes, and was shown to be elevated in the transgenic animals.…”
Section: Trap Expression At Extraskeletal Sitesmentioning
confidence: 99%